Communication Ethics Facing the Ambivalence of Digital Technology - Irsasri, Irsasri; Marina, Rema; Nugroho. E.W, Tri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article aims to review the concept of action and answer how communication ethics faces the ambivalence of digital technology. Using a critical-normative research method on the works of Aristotle and Hannah Arendt, this study finds that in the face of the ambivalence of digital technology, communication ethics needs to put digital actions back on the consciousness of the perpetrator. In addition, communication ethics must overcome banal clicks and deal with the robotic manipulators of digital systems. There are two ways to use it: first, a complicated way in the form of resistance to digital manipulators, and the second is a soft way, which is to reposition the three virtues, namely courage, honesty, and elegance, to build digital altruism in digital communication ethics.